The mega-events database: systematising the evidence on mega-event outcomes - Müller, Martin; Wolfe, Sven Daniel; Gogishvili, David; Gaffney, Christopher; Hug, Miriam; Leick, Annick (My University, 2022)
Although events such as the Olympic Games and World’s Fairs are among the largest of mega-projects, there is little systematic data to evaluate their outcomes over a longer period of time and across multiple sites. This research note describes the first longitudinal database on mega-event outcomes. It lays out the rationale and major goals of the database, its methodological approach and content, and its challenges and limitations. The database allows analysing larger patterns of mega-event contexts and outcomes, and helps evaluating mega-events as public policies.